Former SARS-CoV-2 infection was related to decreased VO2 peak and exercise hypertension in athletes - Keller, Karsten; Friedrich, Oliver; Treiber, Julia; Quermann, Anne; Friedmann-Bette, Birgit (Diagnostics, 2023)
The impact of former COVID-19 infection on the performance of athletes is not fully understood. We aimed to identify differences in athletes with and without former COVID-19 infections. Competitive athletes who presented for preparticipation screening between April 2020 and October 2021 were included in this study, stratified for former COVID-19 infection, and compared. Overall, 1200 athletes (mean age 21.9 ± 11.6 years; 34.3% females) were included in this study from April 2020 to October 2021. Among these, 158 (13.1%) athletes previously had COVID-19 infection. Athletes with COVID-19 infection were older (23.4 ± 7.1 vs. 21.7 ± 12.1 years, p < 0.001) and more often of male sex (87.7% vs. 64.0%, p < 0.001). While systolic/diastolic blood pressure at rest was comparable between both groups, maximum systolic (190.0 [170.0/210.0] vs. 180.0 [160.0/205.0] mmHg, p = 0.007) and diastolic blood pressure (70.0 [65.0/75.0] vs. 70.0 [60.0/75.0] mmHg, p = 0.012) during the exercise test and frequency of exercise hypertension (54.2% vs. 37.8%, p < 0.001) were higher in athletes with COVID-19 infection. While former COVID-19 infection was not independently associated with higher blood pressure at rest and maximum blood pressure during exercise, former COVID-19 infection was related to exercise hypertension (OR 2.13 [95%CI 1.39-3.28], p < 0.001). VO2 peak was lower in athletes with compared to those without COVID-19 infection (43.4 [38.3/48.0] vs. 45.3 [39.1/50.6] mL/min/kg, p = 0.010). SARS-CoV-2 infection affected VO2 peak negatively (OR 0.94 [95%CI 0.91-0.97], p < 0.0019). In conclusion, former COVID-19 infection in athletes was accompanied by a higher frequency of exercise hypertension and reduced VO2 peak.